Аналіз високоефективних кластерів для обробки великих даних - Горішня, К. О. (ХНУРЕ, 2023)
Apache Spark is a powerful tool for big data processing, with benetits such as speed, scalability, and support for multiple programming languages. It outperforms Apache Hadoop in several areas, including processing time and ease of use. However, it also has some drawbacks, such as high resource demands and complex configuration. Overall, Apache Spark is a great choice for developing large-scale data processing and machine learning projects.